Sociodemographic, anthropometric, and dietary characterization of Venezuelan older adults - Ekmeiro Salvador, Jesus Enrique; Arévalo Vera, Cruz Rafael (Horizonte Sanitario, 2023)
Objective: Anthropometric and dietary characterization of elderly Venezuelans according to their socioeconomic stratification, determining their nutritional adequacy based on national references. Materials and methods: Through the Graffar technique, 484 older adults were categorized socioeconomically; evaluating their intake pattern through the combined technique of R24H and FCCA, to compare it qualitatively with the weighted reference values ​​of Venezuelan macro and micronutrients. Results: 35.3% (n=171) had deficits and no obesity was reported in the group. Only the 60-69 age subgroup demonstrated an energy profile adjusted to national references; those older than 70 years averaged a diet of insufficient energy and protein. All age subgroups showed inadequacy for Ca, Mg, Zn and vitamins A and C. The inadequacy was described more extensively in the same proportion as age increased. The most energy-poor diets proved to be those with the least dietary diversity. Conclusions: The current food-nutritional vulnerability of this population group is widely shown, especially in the lower social strata and educational levels. Key words: elderly, anthropometry; nutrition; Venezuela.